Review of Karin Bijsterveld and Jose van Dijck, eds. 2009. Sound Souvenirs: Audio Technologies, Memory and Cultural Practices. Amsterdam: Amsterdam University Press. - Dayal, Geeta (Current Musicology, 2010)
R. Murray Schafer coined the term "sound souvenirs" in The Soundscape (1994 [1977]: 240) to describe what the editors of the eponymous book Sound Souvenirs describe as "endangered sounds, such as the sounds of pre-industrial life, that could be captured by recording technologies or stored in archives, and thus remembered after their extinction" (2009:13). Schafer himself, however, only casually mentioned the phrase in tandem with the more predominant concept of "sound marks; , the sonic equivalents oflandmarks (1977: 1 0,239). Subsequent scholarship also did not explicitly address sound souvenirs as it did other ideas from Schafer's work, such as "schizophonia;' or the splitting of a sound from its source (e.g., Feld 1994, Truax, 2001, Sterne 2006). Over 40 years later, editors Karin Bijsterveld and Jose van Dijck build on The Soundscape's lineage, as interpreted and expanded by Steven Feld (1994), Thomas Porcello (2005), and other works that foreground sound technologies as central to cultural memory; they argue in their introduction that the "sound souvenirs" lining our shelves still have yet to receive significant scholarly attention, and this book at-tempts to address that gap. Its contributors explore the cultural practices of archiving, collecting, resuscitating, and restoring past sounds in order to probe the links between sound and memory; this includes examining the ephemera surrounding recorded sound-reel-to-reel tapes, vinyl records, and so on-along with the sound-making devices themselves, old and new, from transistor radios to cassette recorders to iPods.